2019
DOI: 10.3390/ijms20236010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cadmium on ZO-1 Tight Junction Integrity of the Blood Brain Barrier

Abstract: Cadmium (Cd) is a highly toxic environmental pollutant released from the smelting and refining of metals and cigarette smoking. Oral exposure to cadmium may result in adverse effects on a number of tissues, including the central nervous system (CNS). In fact, its toxicity has been related to neurological disorders, as well as neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases. Under normal conditions, Cd barely reaches the brain in adults because of the presence of the blood–brain barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 114 publications
(142 reference statements)
2
45
0
Order By: Relevance
“…Accordingly, with Tobwala and colleagues, recently, some authors demonstrated no Cd-dependent ZO-1 TJ protein expression alteration in a rat brain endothelial cell (RBE4) line. Nevertheless, the same authors clearly demonstrated an altered distribution of the ZO-1 TJ as well as the formation of F-actin stress fibers and an abnormal vimentin localization upon Cd administration [131].…”
Section: Cadmium and Blood-brain Barriermentioning
confidence: 84%
See 1 more Smart Citation
“…Accordingly, with Tobwala and colleagues, recently, some authors demonstrated no Cd-dependent ZO-1 TJ protein expression alteration in a rat brain endothelial cell (RBE4) line. Nevertheless, the same authors clearly demonstrated an altered distribution of the ZO-1 TJ as well as the formation of F-actin stress fibers and an abnormal vimentin localization upon Cd administration [131].…”
Section: Cadmium and Blood-brain Barriermentioning
confidence: 84%
“…Once Cd induces BBB disruption and permeability increase, it can penetrate and accumulate in the CNS, thus leading to cerebral damage [131].…”
Section: Cadmium and Astrocytesmentioning
confidence: 99%
“…Although so far the unfavorable influence of Cd on the nervous system has been revealed in only a few epidemiological studies [ 29 , 30 , 31 ], this effect has been reported in some investigations carried out in animal models [ 18 , 22 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The injurious action of this heavy metal on the central nervous system is multidirectional and complex [ 18 , 22 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Literature data indicate that Cd may stimulate the generation of reactive oxygen species (ROS) leading to oxidative stress and interact with essential elements (including calcium—Ca) in the nervous tissue, as well as impair neurogenesis, induce apoptosis of neurons, and influence the glutamatergic system, gene expression, and homeostasis of neurotransmitters, including acetylcholinesterase [ 18 , 22 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 …”
Section: Introductionmentioning
confidence: 99%
“…The injurious action of this heavy metal on the central nervous system is multidirectional and complex [ 18 , 22 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Literature data indicate that Cd may stimulate the generation of reactive oxygen species (ROS) leading to oxidative stress and interact with essential elements (including calcium—Ca) in the nervous tissue, as well as impair neurogenesis, induce apoptosis of neurons, and influence the glutamatergic system, gene expression, and homeostasis of neurotransmitters, including acetylcholinesterase [ 18 , 22 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. It is known that lipids are among cellular macromolecules most vulnerable to oxidative modifications [ 38 , 39 , 49 ] and therefore, the brain tissue, due to the abundance of lipids and high oxygen utilization, is especially susceptible to damage by pro-oxidants via the oxidative stress-related mechanisms [ 22 , 38 , 39 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis has suggested that increased levels of Cd in human serum might play a pivotal role in neurodegenerative disorder progression (Xu et al, 2018). In vitro and in vivo studies demonstrated a direct role of Cd in ROS production and endoplasmic reticulum stress (Shukla et al, 1996;Branca et al, 2019a), ultimately leading to the impairment of blood-brain barrier (BBB) integrity. Indeed, once the BBB integrity is compromised, heavy metals and other toxicants can enter the CNS and activate glial cells, causing brain inflammation and neural degeneration (Branca et al, 2020).…”
Section: Introductionmentioning
confidence: 99%